Evaluation of the Recreational Function at the Keren Mo'odu Park, Gorontalo City - Suleman Rauf; Edward Syarif; M. Yahya (Journal of Architectural Research and Design Studies, 2023)
The high mobility of urban life requires alternative places that are close for recreation. Keren Mo'odu Park is the right choice to be used as a recreational facility because of its location in the Gorontalo City area. Keren Mo'odu Park is one of the most visited Green Open Spaces in Gorontalo City, this raises several problems including the cleanliness of the park which is not maintained, damaged garden lights cause visitors to feel uncomfortable because the condition of the park is dark at night and is often used as a park dating place. This study uses a rationalistic paradigm with qualitative methods and qualitative descriptive analysis techniques, aiming to evaluate the function of Keren Mo'odu Park as a recreational facility. The results showed that the function of Keren Mo'odu Park as a recreation area had been running well and was in accordance with the standard of green open space functions.Keywords: Green Open Spaces; Gorontalo City; Recreational Function.